2015
DOI: 10.1038/npp.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Maintenance Decreases Cannabis Self-Administration and Subjective Effects in Daily Cannabis Smokers

Abstract: Given that cannabis use is increasing in the United States, pharmacological treatment options to treat cannabis use disorder are needed. Opioid antagonists modulate cannabinoid effects and may offer a potential approach to reducing cannabis use. In this double-blind, placebo-controlled human laboratory study, we assessed the effects of naltrexone maintenance on the reinforcing, subjective, psychomotor, and cardiovascular effects of active and inactive cannabis. Nontreatment-seeking, daily cannabis smokers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…However, no consistently significant relationship between menstrual cycle phase and modulation of cannabis self-administration has been observed [116, 117]. Gender-inclusive studies report similar findings, and additionally demonstrate modulation of self-administration by treatment with oral THC [118, 119], oral cannabidiol [120], and an opioid receptor antagonist [121]. These studies, however, either lack adequate power to test for gender differences, or do not report analyses of gender differences.…”
Section: Sex Differences In the Rewarding Properties Of Cannabinoidsmentioning
confidence: 99%
“…However, no consistently significant relationship between menstrual cycle phase and modulation of cannabis self-administration has been observed [116, 117]. Gender-inclusive studies report similar findings, and additionally demonstrate modulation of self-administration by treatment with oral THC [118, 119], oral cannabidiol [120], and an opioid receptor antagonist [121]. These studies, however, either lack adequate power to test for gender differences, or do not report analyses of gender differences.…”
Section: Sex Differences In the Rewarding Properties Of Cannabinoidsmentioning
confidence: 99%
“…Cannabis users with opioid dependence are less likely to experience CWS,64 which may indicate the contribution of the endogenous opioid system. In a laboratory study, the µ-opioid receptor antagonist naltrexone was recently shown to reduce self-administration of active cannabis and its related subjective positive effects on heavy cannabis users 65. The authors are unaware of any study having directly examined the effect of naltrexone on the CWS under naturalistic conditions.…”
Section: Human Biological Backgroundmentioning
confidence: 99%
“…However, the drug history of the person might be an important determinant of the effects of naltrexone, as THC intoxication was blunted by naltrexone in marijuana users but not in naïve subjects (Haney, 2007). A recent human laboratory study showed that chronic administration of naltrexone attenuates reinforcing and positive subjective effects in daily cannabis smokers (Haney, Ramesh, et al, 2015), which is encouraging for further testing in clinical trials (Figure 4). In fact, a clinical trial studying effectiveness of long-acting injectable naltrexone (Vivitrol) in patients with cannabis dependence is currently recruiting participants (ClinicalTrials.gov).…”
Section: Findings From Clinical Trials and Laboratory Studies In Hmentioning
confidence: 81%
“…Self-administration procedures have been used to study preferences for different concentrations of addictive substances (e.g. nicotine or THC), or whether certain treatments are able to modify drug self-administration (Haney, Ramesh, et al, 2015; Hart, Haney, Ward, Fischman, & Foltin, 2002). Drug self-administration studies have been also useful for evaluating motivation for different types of reinforcers (i.e.…”
Section: Human Laboratory Approachesmentioning
confidence: 99%